Manhatta de Charles Sheeler et Paul Strand : du panorama au kaléidoscope - Antonia RIGAUD (E-REA)
The film that we now call Manhatta was originally shown in New York at the Rialto Theatre under the title New York the Magnificent; it was then shown in Paris under the title Fumée de New York during a Dada evening, and finally presented in London under the title Manhatta. These three screenings provide us with a clue to the multiple readings it provoked in the 1920s. This paper explores the ambivalent modernism the film builds upon, and shows how the three screenings direct us to three major thematics in the coming together of the modernist paradigm : spectacle, abstraction and political lyricism. The film invests these thematics and quotes from previous or contemporary visual works, creating a network of visual citations that open a dialogue within these three modernist paradigms. The film’s aesthetic discourse is organized around a network of visual quotations and echoes to other arts and, in so doing, it allows for a reflection on intermediality and intericonicity in the modernist context.